Profitability of algorithmic trading on stock, FX and commodity markets - Coufal, Matěj (2024)
This study examines the profitability of algorithmic trading based on three technical analysis indicators − Relative Strength Index (RSI), Commodity Channel Index (CCI), and Rate of Change (ROC). The analysis is performed for three asset classes − stocks, FX pairs, and commodities. The study reveals varying effectiveness of these indicators in enhancing portfolio profitability. The Relative Strength Index (RSI) emerges as a robust indicator for improving stock portfolio performance, demonstrating its potential across different indices (Dow Jones Industrial Average, S&P 100, NASDAQ 100). Conversely, technical analysis applied to FX pairs fails to yield positive monthly returns, highlighting challenges in currency market trading. For commodities, though, all three indicators contribute to enhanced portfolio profitability. Overall, this research provides insights into the performance of technical indicators across asset classes, supporting the usefulness of technical for some asset classes/indicators, while declining its importance for other asset classes/indicators.